Improving PAI Learning Outcomes By Using The Card Sort Method at SDN 04 Muaro Sungai Lolo Kec. Mapat Tunggul Selatan - Herbanus Simanjuntak (BiCED Proceeding, 2024)
This Classroom Action Research (CAR) aims to improve the Islamic Religious Education (IRE) learning outcomes of students at SDN 04 Muaro Sungai Lolo, Mapat Tunggul Selatan, through the implementation of the Card Sort method. The problem faced is the low learning outcomes caused by the lack of variation in teaching methods. The research was conducted in two cycles consisting of planning, implementation, observation, and reflection. The results show a significant improvement in student learning outcomes, with an increase in the average score and active student participation. In cycle I, the student learning mastery reached 41.66%, and increased to 83.33% in cycle II. Therefore, the application of the Card Sort method is proven effective in improving IRE learning outcomes and can be an alternative for IRE teaching in elementary schools.